The noise profile and hearing impact of commercial fiberglass reinforced plastic speed boats in Port Blair, Andaman and Nicobar Islands - Jonathan Lalchawilena; Lalhmingmawii (Asian Journal of Medical Sciences, 2023)
Background: Hearing impairment may result from tourism-related vehicle engine noise in Port Blair, Andaman, and Nicobar Islands. Aims and Objectives: Measure noise levels and test commercial fiberglass-reinforced plastic (FRP) speedboat operators for hearing loss. Materials and Methods: Hearing loss and noise impacts were checked in a total of 145 male crew members and workers exposed to commercial FRP-speedboat outboard engine noise. 18–50-year-olds with 1–20 years of experience participated. To detect hearing loss, noise-induced hearing loss (NIHL) risk indicators that could appear as a 4 kHz noise notch and the existence of high-frequency sloping hearing loss were detected using pure tone audiometry. The level of noise exposure was measured in conjunction with a questionnaire to assess an individual’s general knowledge of the effects of noise and hearing loss. Results: A 4 kHz noise notch, some high-frequency slope hearing loss, and an overall hearing loss rate of 42.1% were found in 145 participants. Out of these, 15.9% had the most common bilateral notch. Bilateral high-frequency sloping was 10.3%, Unilateral high-frequency sloping was 4.9%, and unilateral 4 kHz notch was 11.0%. According to the questionnaire, research participants are shockingly unaware of noise-induced hearing loss. The FRP Speedboat outboard engine’s measured noise level ranged from 79.7 to 89.4 dB (A). Conclusion: The FRP Speedboat crews were at risk of hearing loss, specifically NIHL with continuous noise exposure. High frequency sloping hearing loss, mild to moderate hearing loss, and a substantial 4 kHz noise notch are found in noise-exposed employees. Awareness is needed to prevent irreversible hearing loss.